2013
DOI: 10.1016/j.juro.2012.11.067
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Flexible Dose Fesoterodine in Men and Women with Overactive Bladder Symptoms Including Nocturnal Urinary Urgency

Abstract: Purpose Awakening from sleep to urinate is the hallmark of nocturia, a condition that impacts several facets of health related quality of life and for which current therapy is suboptimal. Given the paucity of prospective data on antimuscarinics for the management of nocturia, we investigated the efficacy and safety of flexible dose fesoterodine for the treatment of nocturnal urgency in subjects with nocturia and overactive bladder. Materials and Methods Subjects with 2 to 8 nocturnal urgency episodes per 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 26 publications
0
20
0
2
Order By: Relevance
“…In a randomized, double-blind, placebo-controlled, flexible-dose, 12 week trial in 963 patients with OAB symptoms, including !3 urgency episodes/24 h and !2 and 8 nocturnal urgency episodes/24 h, a significantly greater decrease from baseline to week 12 in nocturnal urgency episodes/24 h (primary endpoint; fesoterodine, À1.3; placebo, À1.1; P ¼ 0.003) and nocturnal micturitions/24 h (P ¼ 0.011) was demonstrated with fesoterodine versus placebo 65 . This trial of fesoterodine was the first to prospectively evaluate the efficacy of an antimuscarinic for decreasing nocturnal urgency episodes.…”
Section: Patients With Uuimentioning
confidence: 91%
See 1 more Smart Citation
“…In a randomized, double-blind, placebo-controlled, flexible-dose, 12 week trial in 963 patients with OAB symptoms, including !3 urgency episodes/24 h and !2 and 8 nocturnal urgency episodes/24 h, a significantly greater decrease from baseline to week 12 in nocturnal urgency episodes/24 h (primary endpoint; fesoterodine, À1.3; placebo, À1.1; P ¼ 0.003) and nocturnal micturitions/24 h (P ¼ 0.011) was demonstrated with fesoterodine versus placebo 65 . This trial of fesoterodine was the first to prospectively evaluate the efficacy of an antimuscarinic for decreasing nocturnal urgency episodes.…”
Section: Patients With Uuimentioning
confidence: 91%
“…In addition to the two open-label, flexible-dose, extension trials, a flexible-dosing design was used in three openlabel 50,67,77 and five double-blind 48,65,76,80,84 trials evaluating the efficacy and safety of fesoterodine.…”
Section: Flexible-dose Trialsmentioning
confidence: 99%
“…963 subjects with ≥ 2 nocturia episodes were randomized to receive either fesoterodine or placebo and followed for 12 weeks. Fesoterodine significantly reduced nocturnal urgency episodes over placebo (-1.28 vs -1.07, P = 0.003), as were nocturia episodes (-1.02 vs -0.85, P < 0.01) [28]. Further study of the newer antimuscarinics' efficacy in nocturia treatment is needed in order to demonstrate clinically significant efficacy.…”
Section: Pol Scientificmentioning
confidence: 95%
“…At the 2012 New England Research Institute (NERI) nocturia advisory conference, experts left open the possibility of using these medications to treat severe nocturnal OAB episodes [8••]. In a double-blind randomized controlled trial, the antimuscarinic agent fesoterodine was indeed found to have a statistically significant reduction in nocturnal urgency episodes compared to placebo, but the mean difference was only −0.21 [59]. There are several potential reasons for the lack of efficacy in treating nocturia-(1) decreased functional bladder capacity plays a minor role in the etiology of OAB-associated nocturia; (2) OAB is intrinsically too heterogeneous, thus, masking any clinically significant subset of responders; or (3) OAB medications do not sufficiently increase functional bladder capacity to result in clinical improvement.…”
Section: Targeted Pharmacotherapy-increasing Functional Bladder Capacitymentioning
confidence: 99%